2023
DOI: 10.1177/08862605221149090
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Online Child Sexual Abuse in a U.S. National Sample

Abstract: As technology has become increasingly integrated into the everyday lives of young people and social interactions have moved online, so too have the opportunities for child sexual abuse. However, the risk factors for online sexual abuse, and their similarities or differences with those of offline sexual abuse have not been clarified, making it difficult to design prevention strategies. Using a nationally representative online survey panel of young adults ages 18 to 28, the current study sought to identify risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Other possible risk factors include early puberty and early in-person exposure to various forms of abuse, bullying, and adversity that may be associated with subsequent online abuse. 4 Although existing studies suggest an elevated risk of TFA among SGM youths as a whole, few studies have compared rates across specific gender and sexual identity groups, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other possible risk factors include early puberty and early in-person exposure to various forms of abuse, bullying, and adversity that may be associated with subsequent online abuse. 4 Although existing studies suggest an elevated risk of TFA among SGM youths as a whole, few studies have compared rates across specific gender and sexual identity groups, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Although reasons for their elevated risk remain unclear, it has been suggested that sexual and gender minority (SGM) youths engage in more sexting behavior and more often use the internet for acquiring sexual information and finding sexual interactions, all of which can increase risk. Other possible risk factors include early puberty and early in-person exposure to various forms of abuse, bullying, and adversity that may be associated with subsequent online abuse …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this trend, the Pew Research Center found that nearly all U.S. adolescents report daily Internet use (97%), smartphone access (95%), and engagement on social networking platforms such as YouTube (95%), TikTok (67%), and Instagram (62%; Vogels et al., 2022; n = 1316, 13–17 years old). While ICT allows adolescents to develop their identities, establish different interpersonal relationships, explore their sexual interests, and expand extrafamilial bonds (Borca et al., 2015; Eleuteri et al., 2017; Lenhart et al., 2015), its use may also increase the likelihood of becoming victims of technology‐facilitated sexual abuse (hereinafter TFSA; De Santisteban & Gámez‐Guadix, 2018; Finkelhor et al., 2022, 2023; Gámez‐Guadix et al., 2022; Patchin & Hinduja, 2020; Turner et al., 2023; Wolak et al., 2018).…”
Section: Introductionmentioning
confidence: 99%